Three Tlingit men posed in dance costume, Alaska, ca. 1903. - Nowell, Frank H., 1864-1950
Three Tlingit men posed outside in dance costume; all three have painted faces, their clothing is embroidered and beaded. Two of the men wear hats, hold feathers attached to handles in each hands, and also wear nose rings. The third man has feathers and fur in his hair. Another man can be seen in background in western style clothes. Caption on image: Swatka and companions in dancing costumes Stamped on image: Photo by F. H. Nowell